2017
DOI: 10.3389/fpubh.2017.00315
|View full text |Cite|
|
Sign up to set email alerts
|

Teaching Undergraduate Students to Visualize and Communicate Public Health Data with Infographics

Abstract: The purpose of this study was to explore the degree to which an infographic assignment facilitated student learning around health science issues, as well as the ways in which the assignment was an effective teaching tool. The objectives of the assignment were to (1) understand the purposes of and potential uses for infographics, (2) cultivate creative visual communication skills, and (3) disseminate a complex health topic to diverse audiences. The infographic assignment was developed at Montana State Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 11 publications
2
48
0
2
Order By: Relevance
“…While television news channels were perceived as the most reliable source of COVID-19 information, social media posts with infographics had a greater influence on the perceived reliability by comparison with posts consisting of plain text alone. Infographics have been shown to be effective tools in disseminating knowledge, including health information, to audiences from various backgrounds [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…While television news channels were perceived as the most reliable source of COVID-19 information, social media posts with infographics had a greater influence on the perceived reliability by comparison with posts consisting of plain text alone. Infographics have been shown to be effective tools in disseminating knowledge, including health information, to audiences from various backgrounds [ 25 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alabdulqader [7] asked learners to prepare infographics as a method to report outcomes of their studies on ethical issues in computing in their local community. Shanks et al [11] asked small learner groups to study a selected health issue and prepare an infographic as the outcome of their group inquiry. These learners reported that infographics taught them how to communicate science topics to non-experts and appreciated infographics as a way to deepen their learning.…”
Section: Infographics In Educationmentioning
confidence: 99%
“…Creating infographics can enhance multiple dimensions of competency including enhanced efficiency in literature retrieval, critical thinking skills, ability to interpret and communicate data, and creative design thinking 45,46 . Building on these competencies can assist in increasing information clarity, enhancing communication, and decision‐making skills through proper interpretation of complex data.…”
Section: Infographics In Higher Educationmentioning
confidence: 99%